(untitled) (Foro de Educacion, 2015)
Through this article we propose a reflection on the important role of the school of face to face environmental, social and human impact for which neither the man nor the institutions are prepared. The high impact of human activity on the planet puts us in a situation of vulnerability to which the school would have a significant and fundamental role. Within its walls has to recognize the problem, its causes and uncertainties and provide educational responses that allow us to participate successfully with one of the main problems and challenges facing humanity. But the educational model provides a valid response against this complex problem? We believe that to educate on sustainability and provide educational responses to the height of this problem, the school would have to change their organizational forms, and also those relating to the educational process.